2023
DOI: 10.3389/fneur.2023.1131791
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features of traumatic spinal cord injury in China: A systematic review and meta-analysis

Abstract: BackgroundTraumatic spinal cord injury (TSCI) is a highly fatal and disabling event, and its incidence rate is increasing in China. Therefore, we collated the epidemiological factors of TSCI in different regions of China to update the earlier systematic review published in 2018.MethodWe searched four English and three Chinese electronic databases from 1978 to October 1, 2022. From the included reports, information on sample characteristics, incidence, injury characteristics, prognostic factors, and economic bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Exercise also acts as neuroprotective therapy. Findings of the studies have been justified with the fact that exercise-based approach cannot induce neural firing however it is believed to modulate the increased rate of spontaneous neuronal firing specific to activate the CPG for Locomotion thus justifying the synergistic effects with the better functional outcome at the end [24][25][26][27]. However, extensive variability was observed in terms of intervention dosage, frequency and variety of exercises such as intensity of activity, duration of activity, repetition of activity, number and frequency of sessions [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise also acts as neuroprotective therapy. Findings of the studies have been justified with the fact that exercise-based approach cannot induce neural firing however it is believed to modulate the increased rate of spontaneous neuronal firing specific to activate the CPG for Locomotion thus justifying the synergistic effects with the better functional outcome at the end [24][25][26][27]. However, extensive variability was observed in terms of intervention dosage, frequency and variety of exercises such as intensity of activity, duration of activity, repetition of activity, number and frequency of sessions [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 17 studies undertaken in China revealed that the epidemiological features of SCI differed signi cantly across various regions of the country [15,16]. This implies that tailored preventive measures need to be implemented based on the speci c characteristics of each region.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent consequence and major cause of mortality was respiratory issues. 19 Spinal cord injury (SCI) is a frequent disorder, with one million new cases reported each year and 27 million individuals living with SCI-related symptoms. SCIs impose a cost on healthcare systems and economies in the form of lost productivity and expensive healthcare expenses.…”
Section: Discussionmentioning
confidence: 99%